OVERVIEW OF PARENT ANXIETY LEVELS ABOUT THE INSTALLATION OF INFUSIONS IN CHILDREN IN HOSPITAL X - Roza Indra Yeni; Rohina Wahyuning; Rika Hardini; Ricky Riyanto Iksan (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Children have different needs from adults so children are called unique individuals. Parents must maintain the development and health of children who are in a state of declining health that requires hospitalization. Various reactions that can be caused by stress from hospitalization in children such as denial, withdrawal, refusal to eat, and loss of affection. The cause of anxiety is influenced by many factors, both factors from officers (nurses, doctors and other health workers), new environments. The purpose of the study was to determine the level of parental anxiety regarding the installation of IVs in children at the Hospital, The research method is descriptive quantitative. The population in this study were parents at the Hospital X, as many as 55 respondents, parents of children. Data collection in this study used Questionnaire sheet by filling in a questionnaire sheet of 12 questions responding to parents’ anxiety a questionnaire sheet then tested with Univariate Analysis. The results of the study showed low anxiety as much as 49.1% and high anxiety as much as 50.9% with a mean of 1.51, median 2.00 and standard deviation 0.505. The conclusion is that parenteral anxiety can affect the mental status of children, regarding infusion installation in children. Suggest to nurses to provide holistic nursing services both in biological, psychological, social and spiritual aspects so that children can avoid atraumatic care.